Methods of Judicial Appointments in Different Jurisdictions: Lessons for Pakistan - Khan, Yasir Rashid; Khan, Naeem Ullah (Law and Policy Review, 2025)
This paper examines the contemporary mechanism of judicial appointments in Pakistan, focusing on the artificial seniority-versus-merit binary and the power of the Chief Justice of Pakistan (CJP) to appoint judges. It discusses various models of judicial appointments, including single-body mechanisms, representative appointments, professional appointments, cooperative appointments, judicial elections, commission or council appointments, and blended methods. While the commission or council mode proved successful in South Africa during its transition from white-minority rule to a constitutional democracy, it has not been yielded similar results in Pakistan. The Judicial Commission of Pakistan (JCP) has faced criticism for its lack of transparency, manipulation of meetings, pre-pondering role of the chairman, court packing, and a borrowed bureaucrat as secretary of the commission. Drawing on lessons from South African experience, the paper recommends reforms to transform the judicial appointments process in Pakistan.